Application of Marine Microbial Natural Products in Cosmetics - Ding, Jinwang; Wu, Baochuan; Chen, Liqun (Frontiers in Microbiology, 2022)
As the market size of the cosmetics industry increases, the safety and effectiveness of new products face higher requirements. The marine environment selects for species of microorganisms with metabolic pathways and adaptation mechanisms different from those of terrestrial organisms, resulting in their natural products exhibit unique structures, high diversity, and significant biological activities. That means there are more possibilities for their natural products. Natural products are usually safe and non-polluting. Therefore, considerable effort has been devoted to the search for effective and safe natural cosmetic ingredients in marine microorganisms. However, marine microorganisms can be difficult, or impossible, to culture because of their special environmental requirements. Metagenomics technology can help to solve this problem. Moreover, using marine species to produce more green and environmentally friendly products through biotransformation has become a new choice for cosmetic manufacturers. In this study, the natural products of marine microorganisms are reviewed and evaluated with respect to a variety of cosmetic applications.